Fluctuation conductivity in Y-Ba-Cu-O films with artificially produced defects - Solovjov, A. L. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
The fluctuation-induced conductivity (paraconductivity) measured in YBa2Cu3O7-<font face`Symbol`>d(YBCO) films grown on 10° miscut SrTiO3 (001) substrates is analyzed using various theoreticalmodels describing weak fluctuations in high-Tc superconductors and considering bothAslamazov-Larkin and Maki-Thompson fluctuation contributions in the clean limit approach. The analysis reveals a highly anisotropic pair-breaking caused by structural defects produced. This result is in favor of an idea that pseudogap in high-Tc oxydes is mainly governed by the fluctuating pairing.